All things morphology its independence and its interfaces - Moradi, Sedigheh; Aronoff, Mark (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2021)
"This book attempts to provide a view of where the field of morphology has been and where it is today within a particular theoretical framework, gathering up new and representative work in morphology by both eminent and emerging scholars, and touching on a very wide range of topics, approaches, and theoretical points of view. These seemingly disparate articles have a common touchstone in their focus on a word-based, paradigmatic approach to morphology. The chapters in this book elaborate on these basic themes, from the further exploration of paradigms, to studies involving words, stems, and affixes, to examinations of competition, inheritance, and defaults, to investigations of morphomes, to ways that morphology interacts with other parts of the language from phonology to sociolinguistics and applied linguistics. The editors and contributors dedicate this volume to Prof. Mark Aronoff for his profound influence on the field"--